2018
DOI: 10.1002/aelm.201800074
|View full text |Cite
|
Sign up to set email alerts
|

Metal Hexaboride Work Functions: Surface Configurations and the Electrical Double Layer from First‐Principles

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 43 publications
2
2
0
Order By: Relevance
“…The work functions of (001)-metal-terminated rare-earth hexaborides from our calculations are shown in Figure , along with experimental work function values for each material, where available. For the most studied hexaboride, LaB 6 , our DFT-calculated work function is generally lower than experimentally measured values, and the work function of LaB 6 from our calculation (2.01 eV) is consistent with previous computational studies, which found values of 2.07 and 2.27 eV . The observed discrepancy between the calculated and experimental LaB 6 work function may be caused by factors related to the measurement method or method of data analysis ( e.g.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The work functions of (001)-metal-terminated rare-earth hexaborides from our calculations are shown in Figure , along with experimental work function values for each material, where available. For the most studied hexaboride, LaB 6 , our DFT-calculated work function is generally lower than experimentally measured values, and the work function of LaB 6 from our calculation (2.01 eV) is consistent with previous computational studies, which found values of 2.07 and 2.27 eV . The observed discrepancy between the calculated and experimental LaB 6 work function may be caused by factors related to the measurement method or method of data analysis ( e.g.…”
Section: Resultssupporting
confidence: 77%
“…For the most studied hexaboride, LaB 6 , our DFT-calculated work function is generally lower than experimentally measured values, and the work function of LaB 6 from our calculation (2.01 eV) is consistent with previous computational studies, which found values of 2.07 60 and 2.27 eV. 61 The observed discrepancy between the calculated and experimental LaB 6 work function may be caused by factors related to the measurement method or method of data analysis (e.g., fitting work function or work function and Richardson constant in thermionic emission experiments) or materialrelated factors such as different stoichiometries, defect concentrations, and surface conditions determined by sample preparation. In addition, it is possible that errors in DFT play a role, as previous studies benchmarking the accuracy of DFTcalculated work functions suggest that DFT−GGA level work functions are ∼0.3 eV lower than experimental values for metals, 69,70 and a separate study of DFT−HSE level work functions has a ∼0.2 eV deviation, on average, from experiments for SrTiO 3 .…”
Section: Hexaboride Work Functionsupporting
confidence: 90%
See 1 more Smart Citation
“…Strain effects have also been explored as parameters for morphological modification of copper and nickel particles, and doping has been applied for obtaining nanorods of magnesium . In addition, modeling and experimental techniques have been applied for exploring the behavior of borides of cubic and other morphologies. Moreover, experimental efforts have investigated shape change in cubic carbides as a function of carbon stoichiometry, which influences the relative growth rate of the dominant {111} and {100} facets. …”
Section: Introductionmentioning
confidence: 99%